Venture Boards: Past Insights, Future Directions, and Transition to Public Firm Boards. (5th September 2017) - Garg, Sam; Furr, Nathan
Abstract : Research summary: Venture boards are theoretically important and economically relevant. They are at the apex of a venture's organizational hierarchy and have significant influence on the most important decisions related to venture strategy and personnel. This article reviews the organizational and strategy research on venture boards, clarifying how venture boards differ from venture investors and from public firm boards. It lays out a systematic research agenda to stimulate more research on venture governance, including venture board composition and structure, venture board processes, and venture board transitions to public firm boards. This agenda attempts to illuminate the research opportunities related to the distinctive nature of venture boards and enable theoretical engagement with the broader corporate governance scholarship on public firms. Managerial summary: A venture's board of directors is highly consequential for its most important strategic and personnel outcomes. Uber and Theranos are just two recent ventures whose boards have come under public spotlight. This article reviews organizational and strategy research on venture boards, mapping the evolution of the academic literature, summarizing key findings, and identifying the most important limitations. It explains how venture boards are different from venture investors and from public firm boards. Importantly, it lays out a systematic research agenda that draws upon the distinctive nature of venture boards and also creates a bridge to the broader literature on public firm boards. New insights on venture board composition, structure, process, and transition to public firm boards will be relevant to venture executives, investors, and directors. Copyright © 2017 Strategic Management Society.